Teaching Listening of University Level through Online Learning System: A Case Study - Fina Rahmawati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aimed to provide broader insight about teaching listening process through online learning and all of its aspects such as planning, ways of teaching, and assessments of listening skill. This study used a case study method. The researcher chose one of the senior listening lecturers of University of Islam Malang as the subject of the research. Observation, interview, field notes and documents were used to collect the data and triangulation method were used to ensure trustworthiness of data. The finding of the study was indicated that the observed lecturer used some certain platforms such as Google Classroom, Zoom, Google Meet, and Google Form to maximize the teaching listening through online learning system. The observed lecturer also implemented various activities. Besides, the observed lecturer applied meta-cognitive and cognitive strategy and did summative and formative assessment in online teaching listening. It was demanded further exploration and investigation about teaching listening deeply in future research regarding all those findings.